The use of haploid systems in plant genetic manipulation - Pirrie, Andrew (1985)
In the present study the use of haploid plants and tissues was considered in relation to plant genetic manipulation. Haploid plants can be exploited directly, in the synthesis of true breeding lines. Alternatively, haploid plants and tissues may provide material for further experimentation involving protoplast fusion. Both approaches were investigated.